Emergence of Invasive Group A Streptococcus Infection in an Infant: A Case Report - Alexis N. Roach; Ryan Kwong; Sarah Sylvester (Clinical Practice and Cases in Emergency Medicine)
Introduction: Group A streptococcus (GAS) manifests as a spectrum of illnesses, ranging from mild to life-threatening. While relatively rare in infants, GAS infections can present with grave consequences. Case Report: An eight-month-old infant was found to have GAS bacteremia complicated by sepsis and disseminated intravascular coagulation, resulting in lower extremity myositis and tissue ischemia. Tissue ischemia progressed to dry gangrene requiring below-knee amputation followed by six weeks of antibiotics. Conclusion: This case serves as a reminder of the critical importance of vigilance, prompt recognition, and aggressive intervention in the management of invasive GAS infections in infants.